Design and Development of Subcritical Reactor by Using Aqueous Fuel for 99Mo Production: Design and Development of Subcritical Reactor by Using Aqueous Fuel for 99Mo Production - Syarip; Sutondo, Tegas; Budisantoso, Edi Trijono; Susiantini, Endang (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
A non-critical reactor system for 99Mo production has been designed and will be developed at the Centre for Accelerator Science and Technology (CAST), National Nuclear Energy Agency (BATAN). The system is called subcritical aqueous reactor “assembly” for 99Mo production (SAMOP) which is fueled with uranyl nitrate and driven by external neutron source from a neutron generator. The design characteristics of criticality analysis, safety aspect, and calculation of 99Mo specific activities, choice and estimation of technology for 99Mo separation from the irradiated uranyl nitrate are presented in this paper. The analysis result showed that the SAMOP system using low enriched uranyl nitrate UO2(NO3)2 of 300 g U L–1 has an effective neutron multiplication factor of 0.98 to 0.99 with an average neutron flux of 1010 n cm–2 s . The total volumes of UO2(NO3)2 and uranium content in the core are 23 L and 3.8 kg, respectively. The SAMOP system using low enriched uranyl nitrate with total volume of 23 L and 3.8 kg uranium content may produce 111 GBq/batch (3 000 mCi/batch) of 99Mo.